Adaptation of Cinderella Gown into a Strapless Evening Gown Model with Brocade Tulle and Swarovski Embellishments - Farisa Syahla Nur Alifah*; Pipin Tresna Prihatin; Cucu Ruhidawati (Universitas Syiah Kuala, 2024)
Fashion is basically a primary need for humans, which is necessary to protect the body. Fashion will look better and more attractive if you pay attention to its aesthetic value and beauty elements such as in evening gowns. Evening gowns can be realized if they are inspired by the source of the ideas taken. The source of the idea for making this evening gown is the outfit worn by one of the characters in the fantasy movie Cinderella. The 2015 film Cinderella is a romantic fantasy film from the United States produced by Walt Disney Pictures. The most iconic and attention-grabbing outfit in the live-action version of Cinderella is the beautiful blue dress that Cinderella wears while dancing with the prince. This study aims to find out the process and results of adaptation to the evening gown with the source of Cinderella dress ideas. The research with the Project Based Learning method consists of stages: 1) project planning, 2) project implementation, and 3) project evaluation, resulting in a clothing adapted to the strapless model evening gown with brocade and swarovski tile decorations. Based on research that has been conducted on 2 expert judgments, the results were obtained in the form of very good qualifications with an average acquisition percentage of 83.5%, with little input, namely the color of the fashion can be adjusted to the color tone of the original Cinderella gown, then what impressions you want to maintain and change from the fashion products that have been made, so that the concept of adaptation can be seen.